Green composites based on wheat gluten matrix and posidonia oceanica waste fibers as reinforcements. Issue 10 (6th July 2013) - Ferrero, B.; Boronat, T.; Moriana, R.; Fenollar, O.; Balart, R.
<x xml:space="preserve">Abstract</x> In this work, green composites from renewable resources were manufactured and characterized. A fibrous material derived from Posidonia oceanica wastes with high cellulose content (close to 90 wt% of the total organic component) was used as reinforcing material. The polymeric matrix to bind the fibers was a protein (wheat gluten) type material. Composites were made by hot‐press molding by varying the gluten content on composites in the 10–40 wt% range. Mechanical properties were evaluated by standardized flexural tests. Thermo‐mechanical behavior of composites was evaluated with dynamic mechanical analysis (torsion DMA) and determination of heat deflection temperature. Morphology of samples was studied by scanning electronic microscopy and the water uptake in terms of the water submerged time was evaluated to determine the maximum water uptake of the fibers in the composites. Composites with 10–40 wt% gluten show interesting mechanical performance, similar or even higher to many commodity and technical plastics, such as polypropylene. Water resistance of these composites increases with the amount of gluten. Therefore, the sensitiveness to the water of the composites can be tailored with the amount of gluten in their formulation. POLYM. COMPOS., 34:1663–1669, 2013. © 2013 Society of Plastics Engineers